The effect of alginate–gelatin encapsulation on the maturation of human myelomonocytic cell line U937. (19th November 2018) - Nemati, Sorour; Alizadeh Sardroud, Hamed; Baradar Khoshfetrat, Ali; Khaksar, Majid; Ahmadi, Mahdi; Amini, Hassan; Saberianpour, Shirin; Delkhosh, Aref; Akbar Movassaghpour, Ali; Rahbarghazi, Reza
Abstract: Today, many attempts have been collected in the field of tissue engineering for reconstitution of injured bone marrow capacity by transplantation of functional cell source. By having a three‐dimensional condition, microcapsules are appropriate candidates for cells transplantation to target sites. Here, we examined the effect of alginate–gelatin microcapsules on functional maturation of human myelomonocytic cell line U937 after 7 days in vitro. U937 cells were encapsulated by the mixture of alginate–gelatin and cultured for 7 days. Trypan blue staining was used to show cell survival rate. Morphological changes were determined by haematoxylin and eosin staining. The expression of monocyte (CD14) and leukocyte (CD33) factors were measured by flow cytometry. The functional maturation of encapsulated cells was shown by immunocytochemistry targeting myeloperoxidase (MPO) activity and level of CD68. Transcription level of adhesion molecules CD68L, CD18, CD11b, and CD49d/VLA was detected by real‐time polymerase chain reaction. In vivo constitutive capacity of encapsulated U937 was investigated in rabbits via administration to bone marrow. We showed enhanced U937 viability and monocyte and band cell‐like appearance 7 days after encapsulation. These changes coincided with increasing CD33 and CD14 levels and a decrease of CD15, confirming cell maturation ( p  < 0.05). High level of MPO and CD68‐positive cells showed the functional maturation of U937 cells into neutrophils and macrophages. Compared with that of nonencapsulated cells, the level of adhesion factor was up‐regulated. We found labelled cells in the peripheral blood after cell transplantation to bone marrow. These data suggest that alginate–gelatin encapsulation of U937 cells promotes functional leukopoiesis and monocytopoiesis.